Panc como alternativa alimentar: aplicações e receitas em formato eletrônico. - GEMAQUE, Eveline de Matos (2023)
The world diet is constantly moving towards eating habits that bring negative consequences to health, cultural identity, and food diversity. This profile is evidenced when there is a greater intake of processed products to the detriment of minimally processed or fresh products, leading to a nutritional imbalance proportional to the high amounts of calories ingested. Thus, the Non Conventional Food Plants act as a food alternative that is little recognized and explored in its nutritional potential. The objective of this work was to elaborate an ebook with recipes involving the PANC common in the Amazon region, as well as the validation in laboratory and the development of technical data sheets to understand the nutritional information. This is an experimental, descriptive and quantitative study, in which nine recipes were selected, three for each plant analyzed (green banana, nettle and vinegar plant). The culinary practices of the plants, green banana, purple vinegar and nettle, considered in the Amazon region as non conventional genera, were studied. The process of validation of the preparations with these vegetables (green banana biomass, rice with purple vinegar and nettle soup) allowed the elaboration of new recipes adapted from the literature and their respective technical sheets. Moreover, it was also possible to list six other recipes for the compendium of the ebook on PANC in our region (green banana biomass with cupuaçu filling and green banana biomass cupcake stuffed with chicken, vinegar plantain tea with ginger, vinegar plantain flower jelly, nettle tempura and nettle cake). Thus, the information found on these unconventional foods, was innovative for our region, because the PANC researched are easily accessible and are part of the flora of the Amazon region.